Spontaneous self-ordered states of vortex-antivortex pairs in a polariton condensate - Liew, Timothy Chi Hin (2014)
Polariton condensates have proved to be model systems to investigate topological defects, as they allow for direct and nondestructive imaging of the condensate complex order parameter. The fundamental topological excitations of such systems are quantized vortices. In specific configurations, further ordering can bring the formation of vortex lattices. In this work we demonstrate the spontaneous formation of ordered vortical states, consisting in geometrically self-arranged vortex-antivortex pairs. A mean-field generalized Gross-Pitaevskii model reproduces and supports the physics of the observed phenomenology.